2003
DOI: 10.1017/s1323892200000399
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Rehabilitation in the South Australian Workers' Compensation System

Abstract: This paper will analyse the provision of rehabilitation to injured workers with a registered WorkCover claim in South Australia. It presents the comments of key parties on the practice of rehabilitation, approaches to service delivery, and contradictions and paradoxes of the reality of the practice. The comments of workers, employers, case managers, medical practitioners, and of the rehabilitation providers themselves give ample evidence of the complexity of the demands placed upon providers in this system. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…26,27,31,32 Interestingly, fewer HCPs nominated work-related assessment tools such as worksite assessments and functional capacity evaluations to identify barriers to return-to-work, despite these being key services provided by return-to-work intervention providers (such as, occupational therapists). 33 Although functional capacity evaluations and worksite evaluations are commonly used to facilitate return-to-work, Gross and Battie 34 found that functional performance was indeed a weak predictor for workers' compensation claim closure and recovery for workers with upper extremity conditions. Perhaps, through focusing on functional capacity and workplace issues, clinicians may ignore the psychological or social factors that may also pose as barriers in the return-to-work process.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,31,32 Interestingly, fewer HCPs nominated work-related assessment tools such as worksite assessments and functional capacity evaluations to identify barriers to return-to-work, despite these being key services provided by return-to-work intervention providers (such as, occupational therapists). 33 Although functional capacity evaluations and worksite evaluations are commonly used to facilitate return-to-work, Gross and Battie 34 found that functional performance was indeed a weak predictor for workers' compensation claim closure and recovery for workers with upper extremity conditions. Perhaps, through focusing on functional capacity and workplace issues, clinicians may ignore the psychological or social factors that may also pose as barriers in the return-to-work process.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher's familiarity with the area allowed effective management of the high volume of data in relation to the key issues. The distinct perspectives of different stakeholders can be seen in the resulting publications (see Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004. The comments quoted in the introductory material above also come from this source.…”
Section: Research Findings Methodologymentioning
confidence: 99%
“…It is clear that there is a need for an overall assessment of future possibilities in the delivery of improved responses in relation to claims/injury management and rehabilitation in South Australia. Recent publications have outlined concerns and issues in claims/injury management and rehabilitation (Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004a. This article addresses the issue of identifying the key aspects of the situation to which attention should be paid immediately.…”
mentioning
confidence: 99%
“…Rehabilitation counsellors working in workers' compensation settings are required to respond to, and manage, multiple processes while achieving return to work and mutually acceptable outcomes quickly to contain costs (Kenny, 1998). The task of working across organizational systems that are frequently in conflict due to the vested interests of various stakeholders (Roberts-Yates, 2003) necessitates an ability to identify problems, acknowledge concerns and resolve issues. Indeed, there is evidence that suggests the adversarial nature of insurance-based rehabilitation, fails to support the traditional ethos of human service work (Kendall, Buys, & Larner, 2000;Lane et al, 2012;Murphy, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies concerning the ethical challenges facing rehabilitation counsellors exist and rehabilitation counselling research has succeeded in amassing a base of knowledge specific to private sector rehabilitation (Beveridge, Garcia, & Siblo, 2015;Kontosh, 2000;Lane et al, 2012;Tarvydas & Barros-Bailey, 2010;Wright et al, 1998), there is scant research regarding the ethical challenges faced by rehabilitation counsellors working in Australian private provider settings, and the impact of these challenges on practice. Kenny (1995) and Roberts-Yates (2003) have perhaps come closest to exploring the subjective experiences of rehabilitation professionals, noting that conflicts of interest, conflicts between stakeholders, and the attitudes of injured workers, pose a threat to rehabilitation services and outcomes.…”
Section: Introductionmentioning
confidence: 99%